Tan-aw sa Mindanaw an evaluative study on the reportage on Mindanao of Philippine Daily Inquirer and Philippine Star - Abdullah, Somayyah 1986-
"The reportage on Mindanao of the national media in the Philippines has had long-running controversies that have been repeatedly criticized ever since. This study sought to evaluate two national newspapers Philippine Daily Inquirer and Philippine Star, to assess how they have been reporting issues in Mindanao, and what improvements have been made, if any. The researchers primarily conducted a survey among the broadsheets' readers, and interviewed journalists of community newspapers based in Mindanao to evaluate the two broadsheets. A review of the front pages of all the issues from January 2001 to December 2005, to identify the news about Mindanao that have been published, was also conducted. Findings show that these two broadsheets have been inefficient in fulfilling their duties as responsible providers of information. The readers and the journalists generally disapprove of their reportage on Mindanao."